The age factor in optic nerve regeneration: Intrinsic and extrinsic barriers hinder successful recovery in the short‐living killifish. Issue 1 (19th December 2021) - Vanhunsel, Sophie; Bergmans, Steven; Beckers, An; Etienne, Isabelle; Van Bergen, Tine; De Groef, Lies; Moons, Lieve
Abstract: As the mammalian central nervous system matures, its regenerative ability decreases, leading to incomplete or non‐recovery from the neurodegenerative diseases and central nervous system insults that we are increasingly facing in our aging world population. Current neuroregenerative research is largely directed toward identifying the molecular and cellular players that underlie central nervous system repair, yet it repeatedly ignores the aging context in which many of these diseases appear. Using an optic nerve crush model in a novel biogerontology model, that is, the short‐living African turquoise killifish, the impact of aging on injury‐induced optic nerve repair was investigated. This work reveals an age‐related decline in axonal regeneration in female killifish, with different phases of the repair process being affected depending on the age. Interestingly, as in mammals, both a reduced intrinsic growth potential and a non‐supportive cellular environment seem to lie at the basis of this impairment. Overall, we introduce the killifish visual system and its age‐dependent regenerative ability as a model to identify new targets for neurorepair in non‐regenerating individuals, thereby also considering the effects of aging on neurorepair. Abstract : In contrast to findings in zebrafish, this study reveals a striking age‐related decline in optic nerve regeneration in the short‐living killifish, with different phases of the repair process being affected depending on the age. Interestingly, while resembling zebrafish at young age, the regenerative ability is more mammalian‐like at old age. As in mammals, both a reduced intrinsic growth potential and a non‐supportive cellular environment seem to lie at the basis of impaired nerve regeneration.